Protozoans infection of Cyprinus carpio L. from Bab Al-Muatham fish markets, Baghdad City - Mansoor, Nahla Talib; M. Jawad Al-Shaikh, Sadiq (The Iraqi Journal of Veterinary Medicine, 2010)
During the period from November 2007 untill October 2008, a total of 255 specimens of the cyprinid fish Cyprinus carpio Linnaeus, 1758, were collected from fish markets east of Baghdad city. Microscopic examination of these fishes revealed that they were infected with five species of ciliated protozoans [Chilodonella cyprini with 1.6% percentage of infestation, Ichthyophthirius multifiliis (3.5%), Trichodina domerguei (21.6%), Apiosoma piscicola (0.4%) and Epistylis solidus (1.2%)]. C. carpio is considered as a new host (third host) in Iraq for Epistylis solidus